EVALUASI PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NO. 18 MENGENAI AKUNTANSI DANA PENSIUN PADA DANA PENSIUN PT. BANK SULUT - Sembung, Stefanny Tabita Mutiara; Sondakh, Jullie J; Manossoh, Hendrik (Universitas Sam Ratulangi, 2015)
Working to meet the needs of this future is not enough. Concerns arise when one thinks of how one day when he is not in the productive age again. In the 70s the retirement program is only held by civil servants and the military alone, but began to enter the era of the 90s and especially after the issuance ofÂ Law No. 11 of 1992 regulating the pensions, the right to a pension fund is open to all workers, private and individual. There are two pension funds accounting reporting rules, regulations under SFAS No. 18 and regulations of the Chairman of Capital Market Supervisory Agency and Financial Institution No. PER-05/BL/2012. This study used a qualitative method starts with collecting relevant data, then comparing the suitability of the application of the pension fund accounting set forth in SFAS No. 18 and regulations of the Chairman of Capital Market Supervisory Agency and Financial Institution No. PER-05/BL/2012 on the pension fund PT. Bank Sulut as the institution that manages the pension fund. The object of research is the pension fund PT. Bank Sulut. Results of the study there are some discrepancies in the application of the financial statements of the pension fund PT. Bank Sulut with SFAS No. 18, while the presentation of the financial statements of the pension fund PT. Bank Sulut has been in accordance with the regulations the Chairman of the Capital Market Supervisory Agency and Financial Institution No. PER-05/BL/2012.